The effect of consumption and production structure on growth and distribution: A micro to macro model - Tommaso Ciarli; André Lorentz; Maria Savona; Marco Valente (Max Planck Institute of Economics, 2008)
The paper contributes to the literature on the relation between structural changes in demand and supply and growth. We develop a macro-economic model with agent-based micro-foundations that articulates the links between production and organisational structures on the supply side, and the endogenous evolution of income distribution on the demand side. The model contains a simplified, though robust, representation of individual firms in the final goods and capital sectors and classes of workers/consumers. The results, in addition to addressing the technical issue of the model's robustness, illustrate the micro- and meso-properties of the simulated growth patterns. In particular, we observe and explain the interactions between technological change, firm organisation, income distribution, consumption behaviour and growth. The analysis performed on the simulated results broadly confirms and further extends the empirical evidence presented in the literature.
Keywords: O12; J31; L23; D11; O41; 330; Structural change; consumption; earnings distribution; growth